A Synthesis of Deep Benthic Faunal Impacts and Resilience Following the Deepwater Horizon Oil Spill - Patrick T. Schwing; Paul A. Montagna; Samantha B. Joye; Claire B. Paris; Erik E. Cordes; Craig R. McClain; Joshua P. Kilborn; Steve A. Murawski (Frontiers in Marine Science, 2020)
The Deepwater Horizon (DWH) oil spill significantly impacted the northern Gulf of Mexico (nGoM) deep benthos (>125 m water depth) at different spatial scales and across all community size and taxa groups including microbes, foraminifera, meiofauna, macrofauna, megafauna, corals, and demersal fishes. The resilience across these communities was heterogeneous, with some requiring years if not decades to fully recover. To synthesize ecosystem impacts and recovery following DWH, the Gulf of Mexico Research Initiative (GOMRI) Core 3 synthesis group subdivided the nGoM into four ecotypes: coastal, continental shelf, open-ocean, and deep benthic. Here we present a synopsis of the deep benthic ecotype status and discuss progress made on five tasks: (1) summarizing pre- and post-oil spill trends in abundance, species composition, and dynamics; (2) identifying missing data/analyses and proposing a strategy to fill in these gaps; (3) constructing a conceptual model of important species interactions and impacting factors; (4) evaluating resiliency and recovery potential of different species; and (5) providing recommendations for future long-term benthic ecosystem research programs. To address these tasks, we assessed time series to detect measures of population trends. Moreover, a benthic conceptual model for the GoM deep benthos was developed and a vulnerability-resilience analysis was performed to enable holistic interpretation of the interrelationships among ecotypes, resources, and stressors. The DWH oil spill underscores the overall need for a system-level benthic management decision support tool based on long-term measurement of ecological quality status (EQS). Production of such a decision support tool requires temporal baselines and time-series data collections. This approach provides EQS for multiple stressors affecting the GoM beyond oil spills. In many cases, the lessons learned from DWH, the gaps identified, and the recommended approaches for future long-term hypothesis-driven research can be utilized to better assess impacts of any ecosystem perturbation of industrial impact, including marine mineral extraction.